Colostrogenesis: candidate genes for IgG1 transcytosis mechanisms in primary bovine mammary epithelial cells. Issue 6 (22nd December 2012) - Stark, A.; Vachkova, E.; Wellnitz, O.; Bruckmaier, R.; Baumrucker, C.
Summary Bovine colostrogenesis is distinguished by the specific transfer of IgG1 from the blood to mammary secretions. The process has been shown to be initiated by hormones and occurs during the last weeks of pregnancy when steroid concentrations of estradiol (E2) and progesterone (P4) are highly elevated. Rodent intestinal uptake of immunoglobulin G is mediated by a receptor termed Fc fragment of IgG, Receptor, Transporter, alpha (FcGRT) and supported by light chain Beta‐2‐Microglobulin (β2M). We hypothesized that steroid hormone treatments (E2 and P4) of bovine mammary epithelial cells in vitro would induce up‐regulation of IgG1 transcytosis candidate gene mRNA expression suggesting involvement in IgG1 transcytosis. Two different primary bovine mammary epithelial cell cultures were cultured on plastic and rat tail collagen and treated with hormonal combinations (steroids/lactogenic hormones). Evaluated mRNA components were bLactoferrin (bLf: a control), bFcGRT, β2M, and various small GTPases; the latter components are reported to direct endosomal movements in eukaryotic cells. All tested transcytosis components showed strong expression of mRNA in the cells. Expression of bFcGRT, bRab25 and bRhoB were significantly up‐regulated (p < 0.05) by steroid hormones. bRab25 and bRhoB showed increased expression by steroid treatments, but also with lactogenic hormones. Analysis for the oestrogen receptor (ER) mRNA was mostly negative, but 25% of the cultures tested exhibited weak expression, while the progesterone receptor (PR) mRNA was always detected. bRab25 and bRhoB and likely bFcGRT are potential candidate genes for IgG1 transcytosis in bovine mammary cells.